ผลกระทบของอุทกภัยต่อพื้นที่ปลูกสร้างและโครงสร้างพื้นฐานในเขตเมืองแพร่ - ธิดารัตน์ คำคง (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
Established for more than 1,200 years, Phrae city not only preserves its characteristics as an old city but is also the governmental, commercial and service center of the province. The infrastructural development and the urban expansion into the agricultural areas which serve as floodway lead to more severe floods. The objectives of this study were to 1) examine the city’s geographical features, structure and physical elements, 2) investigate the floods in the studied areas, the occurrence of the floods and their causes, and 3) analyze the severity of floods and their impacts on the built-up areas and the infrastructure in Phrae city. The methodology covered the analysis of the amount of rainfall and the amount of runoff by using Nays2D Flood program, which reproduced floods. Then the floods were analyzed to find out their extent, the water level and the duration of the inundation. It was found that both the internal and the external factors caused the floods. The external factors included the encroachment of the forested watershed areas, causing the water from the watershed to flow into the city’s rivers. This overflowed the city. The city expansion into the floodway and canals, and the road construction obstructing the drainage were internal factors According to the findings obtained from the study of 1995 floods, three communities were flooded a little (the water level from 0.01 to 0.50 meter).Six communities were moderately flooded (the water level from 0.51 to 1.50 meters).Nine communities were heavily flooded (the water level over 1.50 meters).The depth of the water increased according to the slope of the area from the east along the Yom River to the west of the city. The area which was severely damaged was that around Sri Chum Temple on the Yom River but this area was sparsely inhabited. The area which was inundated for a long period of time was the inner city area where government offices, schools, temples and important places are situated. The affected area where the water level increased so quickly that property relocation and evacuation posed problems was the area to the east of the city wall. This area is densely populated and more business activities are carried out here than anywhere else. It was also found that a building which was built on high stilts or which had more than one floor was less affected than one-story building. In addition, a wooden building was the least affected. To reduce the impacts of the floods, flood-prone areas should be determined so that nobody can settle down there or some measures should be set up so a newly-constructed building has to be built on high stilts, road construction must not obstruct the water flow and natural floodway and drainage have to be preserved.